Can ChatGPT Strengthen Students’ Confidence in Business Email Writing? A Quantitative Study of EFL Learners’ Self-Efficacy - Hindri Febri Ana Sari; Vascolino Pattipeilohy; Hedyan Putra (Universitas Islam Negeri Palopo, 2026)
Despite increasing scholarly attention to generative artificial intelligence (AI) in language education, the extent to which ChatGPT supports learners’ confidence in workplace-oriented writing remains underexplored in EFL contexts. This study investigated the influence of ChatGPT-assisted instruction on EFL learners’ business email writing self-efficacy and explored students’ perceptions toward ChatGPT-mediated writing support. Using a quantitative quasi-experimental design, the study involved 70 sixth-semester students enrolled in a Business Letter course within a DIV Applied Business Administration Program at a state polytechnic in Ambon, Indonesia. Participants were assigned to an experimental group receiving ChatGPT-assisted instruction and a control group receiving conventional instruction during a 12-week intervention. Data were collected using a 30-item questionnaire and analysed through descriptive statistics, paired-samples t-tests, and independent-samples t-tests. The findings indicated substantially greater improvement in business email writing self-efficacy among students receiving ChatGPT-assisted instruction (mean gain = 19.40) than those receiving conventional instruction (mean gain = 6.26). Students also reported favorable perceptions regarding ChatGPT’s usefulness, revision support, confidence enhancement, anxiety reduction, and writing independence. The findings suggest that pedagogically mediated ChatGPT integration may serve as a meaningful resource for strengthening confidence in workplace-oriented EFL writing.